PELATIHAN SAT (SELF REGULATION, ASSERTIVENESS, DAN TIME MANAGEMENT) UNTUK MENINGKATKAN KEDISIPLINAN SISWA - Martaningrum, Alit; Aisya, Ajeng Yunita; Putra, Erlangga Anantayudha Nursahid; Ruhaena, Lisnawati (Universitas Muhammadiyah Surakarta, 2022)
The government is currently implementing distance learning for all schools due to the COVID-19 pandemic. On the other hand, distance learning has resulted in a decline in student discipline levels. To overcome this, the SAT (Self regulation, Assertiveness, and Time Management) training is designed to improve the discipline of high school students. The research subjects were high school students between the ages of 15-18 years who were given SAT training using a one group design pretest posttest. The results showed that the t value was 6.775 with a significance of 0.000 (p < 0.05). So it can be concluded that the SAT training webinar can improve the discipline of high school students.